Study of Effect of Acupressure Methods on Pain in Primary Dysmenorrhea - R Latifnezhead; M Vigeh; Z Aghamiri; S Nabavi (Tehran University of Medical Sciences, 2005)
Background & Aim: Primary dysmenorrhea is highly prevalanet and causes much work loss and discomfort. Regard to critical role of women in family and society it is necessitate that to betaken proper investment for improving their mental and physical health. Methods & Materials: In this study 100 student suffer from primary dysmenorrhea were selected by targeted sampling and take their in two equal groups, case (acupressure group) and control (sham group) randomly. Initially in addition to personal identity, we recorded their history of menstruation, physical activity, vital signs, menstrual pain intensity. Treatment was given during two consecutive menstrual cycles coincident with pain and bleeding by acupressure in case group, and pressure in control group in two time of 15 minutes and 30 minutes interval during 6 hours after onset of dysmenorrhea in each cycle. In case group the treatment was given on lumbar, abdomine, foreleg and ear points, and in control group on placebo points by single blind method. Pain rating was done with use of V.A.S (Visual Analgesic Scale) in 30 min, 1 hr, 2hr and 3hr interval after treatment. Results: The results showed that mean pain scores before (8.21.6) and after (2.61.3) in case group have significant difference. Also there is significant difference between mean pain score before and after treatment in case and control groups (p<0.001). Conclusion: This study showed that acupressure at specific points in lumbar, abdominal, ear reduce the pan intensity and psychic and mental due to primary dymenorrhea. Therefore acupressure could be used as a non-medicament, inexpensive and safe method in decrease of pain of dysmenorrhea in girl and women.